DNA barcoding and elucidation of cryptic aphid species (Hemiptera: Aphididae) in India. Issue 5 (17th May 2013) - Rebijith, K.B.; Asokan, R.; Kumar, N.K. Krishna; Krishna, V.; Chaitanya, B.N.; Ramamurthy, V.V.
Abstract: Rapid, precise and timely identification of invasive pest insects such as aphids is important and a challenge worldwide due to their complex life cycles, parthenogenetic reproduction, sex and colour morphs. In this respect, DNA barcoding employing a 658 bp fragment of 5′ region of the mitochondrial cytochrome oxidase I (CO-I) gene is an effective tool in addressing the above. In the present study, we employed CO-I for discriminating 142 individuals representing 32 species of aphids from India. Sequence analyses revealed that the intraspecific and interspecific distances ranged from zero to 3.8% and 2.31 to 18.9%, respectively. In addition, the study also showed for the first time the prevalence of three cryptic species, namely Brevicoryne brassicae (Linnaeus), Hyperomyzus carduellinus (Theobald) and Brachycaudus helichrysi (Kaltenbach) from India. Our work has clearly demonstrated that DNA barcoding is an efficient and accurate method for identification of aphid species (including cryptic species), an approach that potentially could play an important role in formulating viable pest management strategies, more especially biocontrol.